2020
DOI: 10.1093/gji/ggaa498
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Mw7.5 Palu ‘supershear’ earthquake ruptures geological fault's multi-segment separated by large bends: Results from integrating field measurements, LiDAR, swath bathymetry, and seismic-reflection data

Abstract: Summary On 28 September 2018, 18:02:44 local time, the Magnitude 7.5 earthquake accompanied by a tsunami and massive liquefaction devastated Palu region in Central Sulawesi, Indonesia. Comprehensive post-disaster surveys have been conducted, including field survey of surface ruptures, LiDAR, multibeam-bathymetry mapping, and seismic-reflection survey. We used these data to map fault ruptures and measure offsets accurately. In contrast to previous remote-sensing studies, suggesting that the earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 34 publications
5
73
0
Order By: Relevance
“…However, as mentioned above, the initial interpretations of the high-resolution deeper water bathymetric data of Frederik et al (2019), and the separate high resolution bathymetric survey by Liu et al (2020) did not show any evidence of a clear rupture trace in the bay. In their recent interpretation of this data, Natawidjaja et al (2020), in contrast, suggest several meters of vertical fault movement. Notwithstanding these new interpretations and, as noted by Liu et al (2020), since the Palu-Koro fault was not previously mapped underwater, the existing earthquake models have adopted various assumptions regarding where the fault trace is located.…”
Section: Labelmentioning
confidence: 85%
See 2 more Smart Citations
“…However, as mentioned above, the initial interpretations of the high-resolution deeper water bathymetric data of Frederik et al (2019), and the separate high resolution bathymetric survey by Liu et al (2020) did not show any evidence of a clear rupture trace in the bay. In their recent interpretation of this data, Natawidjaja et al (2020), in contrast, suggest several meters of vertical fault movement. Notwithstanding these new interpretations and, as noted by Liu et al (2020), since the Palu-Koro fault was not previously mapped underwater, the existing earthquake models have adopted various assumptions regarding where the fault trace is located.…”
Section: Labelmentioning
confidence: 85%
“…Without a comparison of pre-and post-earthquake leveling data, it is not clear which, if any, of the earthquake models is most appropriate. The recent work by Natawidjaja et al (2020), published too late to include for consideration here, reinterpreted Frederik et al (2019)'s multibeam bathymetry and identified the major, meandering, submarine channel in the center of Palu Bay, as the seabed expression of the 2018 movement of the strike-slip fault. Based on this study, the fault could be considered to be more effective in tsunami generation than previously proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earthquake was triggered by the rupture of more than 200 km of the Palu-Koro fault extending from the Tanimbaya Peninsula in the north to near Labua in the south [34][35][36][37][38][39][40]. Post-earthquake field surveys mapped a surface rupture 70 km long in the Palu basin [30][31][32][33], and surface ruptures on the seafloor of Palu Bay were documented after the earthquake [33]. The earthquake caused left-lateral displacements as great as about 6 m and vertical displacements of about 5 m at the surface [30][31][32][33].…”
Section: The 2018 Palu Earthquakementioning
confidence: 99%
“…In Sulawesi Island, Indonesia, a pull-apart basin is present near the city of Palu along the Palu-Koro fault (Figure 2), which ruptured during the Mw 7.5 earthquake on 28 September 2018 ('the 2018 earthquake' hereafter), causing extensive damage mainly in the Palu basin, the southward structural continuation of Palu Bay, due to tsunami waves and liquefaction landslides [27][28][29]. The earthquake produced distinct surface ruptures in the Palu basin [30][31][32][33], and many studies have used satellite and seismic data to estimate fault models and rupture propagation [34][35][36][37][38][39][40][41][42]. However, few studies have adequately compared the distribution of active faults, defined on the basis of geomorphic features, with the location of 2018 surface ruptures.…”
Section: Introductionmentioning
confidence: 99%